RELATIONS BETWEEN STATE AND RELIGIOUS ORGANIZATIONS IN INTERNATIONAL AND EUROPEAN LEGAL ACTS - Mihailovs, Ivans Jānis (Via Latgalica, 2009)
Religion is one of the most important social regulators influencing the relations in the society and the choice (action) of an individual in the concrete situation, sacralize definite behaviour and standards, or quite vice versa – disavow them (sin), regulate the relations among people and the relations between human and the highest power (God), in separate cases allowing to overcome legal and ethical dilemmas, to act or refrain from action. Each religion exists in a definite community (society), therefore, the religious norms affect the life of community members and thus also the state, culture, and rights. Nowadays the impact of rights on religion, religious organizations as communities of believing persons, their organization, administration and activity is impossible to deny. This study is an attempt to offer a review on the regulation of the relations betweens state and religious organizations in international and European legal acts. Analysis of the legal aspects of the relations between state and religious organizations allow the conclusion that the freedom of religion has a fundamental basis which today determines the relations/attitude of the state with/to religion and religious organizations. The principle of freedom of religion as an integral part of human rights is respected and implemented in states where the church is fully or partly separated (segregated) from the state as well as in states where there is state church. This principle has been acknowledged also by the European Union and the European Council leaving the implementation details to the Member States themselves. The principle of freedom of religion comprises two principal aspects: person’s individual choice to not/belong to some religion and to not/participate in religious activities, and state’s responsibility is to respect, within the framework of the law, the freedom of activities of religious organizations. Implementation of the principle of freedom of religion is burdened by manifold interpretation of the notions “religion” and “belief”; by the necessity to consider this principle commensurate with other human rights and freedoms; by the vagueness of the limits of this principle. In this context, the practice of the European Court of Human Rights is essential, in interpreting correspondingly the principle of freedom of religion provided for in Article 9 of the European Convention for the Protection of Human Rights and Fundamental Freedoms, particularizing the understanding of this principle in the relations between the state and religious organizations. Present-day practice, at least in the public sphere, facilitate a tolerant attitude and observance of the specific character of religious belonging in various social relations (work, contacts with state administration, military service) etc. Nevertheless, disregarding several implementation problems of the principle of freedom of religion, equality should be observed in the relations between the state and religious organizations, establishing precise limits of cooperation and supervision, which is a precondition for the existence of a legal secular state.